2013
DOI: 10.4103/2231-0738.114847
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Cronobacter sakazakii to plant products, antibiotics, and to lactic acid bacteria

Abstract: Introduction:Cronobacter sakazakii is an emerging and opportunistic pathogen, related with outbreaks of necrotizing enterocolitis, bacteremia, and infant meningitis. Powdered infant formula (PIF)-products contaminated by C. sakazakii cause severe infections in infants. Materials and Methods: In the present study, C. sakazakii isolates were tested for their susceptibility to various antibiotics using the Kirby-Bauer disk diffusion method. Alternatively, C. sakazakii infections can be controlled by various plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Sharma and Prakash, (24) reported that Lactobacillus fermentum has antimicrobial activity against C. sakazakii incubated for various time duration .…”
Section: Figure (3) Antibacterial Activity Of Lactobacillus Fermentum...mentioning
confidence: 99%
“…Sharma and Prakash, (24) reported that Lactobacillus fermentum has antimicrobial activity against C. sakazakii incubated for various time duration .…”
Section: Figure (3) Antibacterial Activity Of Lactobacillus Fermentum...mentioning
confidence: 99%